Composition and Diversity of Aquatic Insects at Hutan Lipur Bukit Soga Perdana, Batu Pahat, Johor - Zakaria, Mohammad-Zulhusni; Mohamed, Maryati (Journal of Science and Technology, 2018)
Human activities such as agriculture would negatively affect the quality of water sources and becomes a factor to the reduction of the composition of aquatic insects. A study was conducted to determine the composition of aquatic insects and correlation made between its composition and habitat in Soga Perdana Amenity Forest or locally known as Hutan Lipur Soga Perdana (HLSP), Batu Pahat, Johor. Samples were collected by using Kicking net for three days. A total of 794 individuals of aquatic insects representing 31 families from seven orders were collected. The orders ranked from the most family rich to the least showed that Diptera has seven families (22.6%); Trichoptera six families (19.4%); Ephemeroptera with five families (16.1%); Odonata, four families (12.9%); Coleoptera, four families (12.9%), Hemiptera, three families (9.7%) and Plecoptera, two (6.5%). Most abundant were from families Leptophelibidae (Ephemeroptera with 131 individuals), Simuliidae (Diptera with 95 individuals) and Heptageniidae (Ephemeroptera with 92 individuals). Further analysis were carried out using several assessment index which were normally used. In this study Hilsenhoff Biotic Index (HBI), Biological Monitoring Working Party (BWMP) and EPT index were calculated. Results showed that HLBSP water body is of good quality and observed to be free from any anthropogenic activities. Eventhough with quantitatively limited supply, the available water bodies in this area supported high taxa richness with 31 families. For future conservation, works to preserve water bodies at HLBSP have to be done, since it is a water supply to maintain the forest regeneration in the reserve. Maintaining HLBSP is critical, because it plays an important ecological role as the green lung for the highly industrial district of Batu Pahat.